The Influence of Accounting Information Use and E-Commerce on MSME Performance: The Moderating Role of Financial Literacy - Baihaqi Ammy; Nur Azizah Sinaga (Lembaga Riset Ilmiah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent the backbone of Indonesia's economy, yet their performance remains constrained by limited utilization of accounting information, low e-commerce adoption, and inadequate financial literacy challenges particularly evident among food-and-beverage entrepreneurs in urban sub-districts. This study examines the effects of accounting information use and e-commerce adoption on MSME performance, with financial literacy as a moderating variable, among food-and-beverage MSMEs in East Medan District, Medan City, Indonesia. An associative quantitative research design was employed, and primary data were collected via structured Likert-scale questionnaires from 83 food-and-beverage MSMEs selected through proportional stratified random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0, following a two-stage assessment of the measurement and structural models. The model explained a substantial proportion of variance in MSME performance (R² = 0.876; adjusted R² = 0.868). Results show that both accounting information use (β = 0.415, p < 0.001) and e-commerce adoption (β = 0.283, p = 0.031) exert positive and significant effects on MSME performance. Financial literacy positively and significantly moderates the relationship between accounting information use and MSME performance (β = 0.257, p = 0.026), amplifying the performance benefit of accounting competency among financially literate owners; however, financial literacy does not significantly moderate the e-commerce–performance relationship (β = -0.013, p = 0.906), likely because contemporary Indonesian e-commerce platforms are sufficiently user-friendly to reduce the required financial knowledge threshold. These findings extend the Resource-Based View (RBV) by showing that financial literacy functions as a complementary human capital resource that selectively enhances the strategic value of accounting information. Implications for MSME capacity-building policy, digital transformation programs, and financial education are discussed.